2005
DOI: 10.1016/j.diamond.2004.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Thin nanodiamond membranes and their microstructural, optical and photoelectrical properties

Abstract: We have grown variety of thin nanocrystalline diamond thin layers on silicon substrates with thicknesses ranging from 100 to 2000 nm. Using a bias enhanced nucleation for nucleation density over 10 10 cm -2 and changing the deposition conditions and/or using argon dilution we have obtained nanodiamond layers of different structural properties. The nucleation process and growth was monitored with Scanning Electron Microscopy (SEM); cross-section SEM and micro-Raman measurements were used to access the nanodiamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Observation of a slope of −66 mV per pH unit indicated that equal numbers of electrons and protons are involved in the electro-oxidation of EN on the surface of NDG/PGE. These results are in a good agreement with an accepted mechanism for EN oxidation [21]. A similar negative shift in the peak potential with increasing the pH of the buffer solution was observed for UA.…”
Section: Ph Effectsupporting
confidence: 89%
See 1 more Smart Citation
“…Observation of a slope of −66 mV per pH unit indicated that equal numbers of electrons and protons are involved in the electro-oxidation of EN on the surface of NDG/PGE. These results are in a good agreement with an accepted mechanism for EN oxidation [21]. A similar negative shift in the peak potential with increasing the pH of the buffer solution was observed for UA.…”
Section: Ph Effectsupporting
confidence: 89%
“…The studies demonstrated that NDs are biocompatible and non-toxic, and can be used for in vivo analysis. NDs possess chemically inert cores with very high surface area, and have smooth surface with excellent homogeneous mechanical and thermal properties [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The CVD was achieved at a constant methane concentration (1% CH 4 in H 2 ) and under a total gas pressure of 30 mbar. Our previous work has shown that using an ellipsoidal reactor, running plasma under low pressures (30 mbar and lower) results in a growth of NCD with a grain size ranging from 30 to 100 nm [30]. The substrate temperature was controlled via a variable substrate holder consisting of dummy openings in the bottom part, and was kept in the range 370-410 8C (as measured by the two-color pyrometer working at wavelengths of 2.13 and 2.35 mm, Williamson-type).…”
Section: Methodsmentioning
confidence: 99%
“…Si wafers and 15 · 15 mm Si plates were used. Nucleation (bias enhanced nucleation) and deposition details were presented elsewhere [2]. Nanodiamond films were also grown on alkali free glass such as Corning 7059 and Schott AF45 (1 · 1 in.…”
Section: Methodsmentioning
confidence: 99%